Thermal, structural and dynamical mechanical properties of hollow glass sphere-reinforced polypropylene composites - Yagci, Ozlem; Eker Gumus, Beril; Tasdemir, Munir (SPRINGER, 2021)
In the present study, the effect of maleic anhydride grafted polypropylene (MAPP) ratio on the thermal and dynamic mechanical properties of polypropylene/hollow glass spheres (PP/HGS) composites was investigated. Hollow glass spheres content was constant at 20 wt % and MA-g-PP was set at four different levels: 1, 5, 10 and 15 wt % in PP/HGS composites. The mechanical properties of polymer composites as a function of temperature were measured using dynamic mechanic analyzer. The oxidation induction times tests and thermal properties were carried out in thermogravimetric differential thermal analyzer in order to determine thermo-oxidative performance and thermal stability of the composites. Moreover, the x-ray diffraction (XRD), the Fourier transform infrared spectrophotometry and the scanning electron microscopy were used to analyze the structural characteristics of the polymer composites. The results demonstrated that the increased MAPP content enhanced dynamic mechanical and thermal oxidative aging properties of PP /HGS composites. The addition of MAPP did not alter the crystal structure according to XRD results.
Keywords: Polypropylene; Glass spheres; TGA; DMA; FT-IR; XRD; SEM; MAPP; ANHYDRIDE-GRAFTED POLYPROPYLENE; CONDUCTIVITY; MICROSPHERES; Polymer Science